2018
DOI: 10.1051/0004-6361/201731713
|View full text |Cite
|
Sign up to set email alerts
|

The Caviar software package for the astrometric reduction of Cassini ISS images: description and examples

Abstract: Aims. Caviar is a software package designed for the astrometric measurement of natural satellite positions in images taken using the Imaging Science Subsystem (ISS) of the Cassini spacecraft. Aspects of the structure, functionality, and use of the software are described, and examples are provided. The integrity of the software is demonstrated by generating new measurements of the positions of selected major satellites of Saturn, 2013–2016, along with their observed minus computed (O−C) residuals relative to pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Such work showed that the solar phase was an issue. Unfortunately, the authors did not (Cooper et al 2018). Clearly a more complex shape model is required to benefit fully from the high accuracy of ISS data.…”
Section: Appendixmentioning
confidence: 99%
“…Such work showed that the solar phase was an issue. Unfortunately, the authors did not (Cooper et al 2018). Clearly a more complex shape model is required to benefit fully from the high accuracy of ISS data.…”
Section: Appendixmentioning
confidence: 99%
“…Table 2 provides a sample of the complete set of reduced observations. Following, for example Cooper et al (2018); Tajeddine et al (2013), the satellite positions in pixel coordinates and the camera pointing information in terms of the right ascension, declination (α c , δ c ) and twist angle θ are provided separately. This provides the user with the flexibility to be able to re-estimate the camera pointing correction at some later date, without having to re-measure the satellite positions, and vice versa for the satellite positions.…”
Section: Test Of the Automatic Methodsmentioning
confidence: 99%
“…Methods for the astrometric reduction of Cassini ISS images using proprietary software have been described in Cooper et al (2006Cooper et al ( , 2008 and Tajeddine et al (2013). The development of these methods over the course of the Cassini mission culminated in the release to the community of the Caviar software package, developed jointly by QMUL (Queen Mary University of London) and IMCCE (Institut de mécanique céleste et de calcul des éphémérides) (Cooper et al 2018). In Caviar, the astrometric data reduction pipeline includes two main steps: a correction for errors in the nominal spacecraft camera pointing direction, followed by the astrometric measurement of the centre of the target planetary satellite.…”
Section: Astrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…During the past a few years, the Cassini ISS images have been routinely used to measure the astrometric positions of planetary satellites [1][2][3][4] . The soft package Caviar has been also implemented for the task [5] , which is convenient to reduce space images. Tajeddine et al [2] and Cooper et al [3] have reduced the ISS NAC images of Enceladus before 2014.…”
Section: Introductionmentioning
confidence: 99%